Comparative study on ELISA, CLIA and rapid diagnostic test in detecting HCV infection in blood donor at a tertiary care center - M. Preethi; M. Saisudha; P. Subhashini; Resmi P. R (Journal of Applied Pharmaceutical Research, 2023)
Background: The prevalence of blood screening assays for hepatitis C infection among blood donors remains comparatively low in line with WHO guidelines, especially when compared to developing nations. Various methodologies, such as ELISA, immunochromatography assays, RIBA, HCV RNA PCR, and CLIA, are employed to detect anti-HCV IgG antibodies in all patients with HCV infection. However, there is a significant scarcity of comparative data available regarding the evaluation of HCV infection screening among CLIA, ELISA, and RDT methods in their ability to detect anti-HCV antibodies effectively. This gap in knowledge highlights the need for further research and analysis in this critical area of healthcare. In this study we evaluate the technical performance between ELISA, CLIA and RDT in detection of HCV infection. Materials and method: A cross-sectional study was carried out, involving 70 blood donor samples. Subsequently, the samples were subjected to screening for Anti-HCV antibodies using three different methods: RDT, CLIA, and ELISA. The results obtained from these screenings were duly recorded. Results: Among the 70 patients included in the study, 63 (90%) were male, and 7 (10%) were female. The following performance metrics were calculated for each method where CLIA shows 100% sensitivity, Specificity 98%, PPV 100%, NPV 98.9%, Accuracy 100%, Kappa coefficient 0.932, p-value <0.001, in case of ELISA: Sensitivity 97.6%, Specificity 99.2%, PPV 100%, NPV 97.1%, Accuracy 99%, Kappa coefficient 0.97, p-value <0.001. followed by RDT: Sensitivity 89%, Specificity 87.9%, PPV 100%, NPV 90.2%, Accuracy 96%, Kappa coefficient 0.59, p-value <0.001. These results provide valuable insights into the performance of each method in screening for HCV antibodies, with CLIA and ELISA demonstrating higher sensitivity, specificity, and overall accuracy compared to RDT. Conclusion: In conclusion, the study suggests that the CLIA screening method for detecting HCV infections is considered superior to both ELISA and RDT in a Tertiary care center.